The pod and the bog - Citro, Asia (Citro, Asia. Zoey and Sassafras., 2018)
An old friend visits Zoey with a glowing seed pod. Zoey, Sassafras and Pip must work together to discover what this mysterious and rare magical plant needs to grow before all the seeds crumble to purple dust!--from book jacket.